Effect of sowing dates on different wheat varieties at Tikapur, Kailali, Nepal - Rajbanshi, Devraj; Sharma, Raksha; Bohara, Binod; Chaudhary, Archana; Rasali, Priyanka; Magar, Sangita Gaha (Nepal Agriculture Research Journal, 2025)
Growth and yield of wheat are affected by variety and sowing dates. Hence a field experiment was carried out at Agronomy Farm, Far Western University in Tikapur, Kailali, Nepal during 2023/24 to study the effect of sowing time and varieties on yield and yield attributing traits of wheat. The experiment was laid out in split plot design comprising four sowing dates viz. 17th November, 27th November, 7th December and 17th December as main plot and three varieties of wheat viz. Vijay, Gautam and Aaditya as sub plot, with three replications. Plant height, spike length, peduncle length, grain per spike, seed length, grain yield and straw yield were significantly higher when sown on 7th December for all the varieties. However, the highest number of effective tillers along with delayed heading, anthesis, maturity and lower grain filling period was observed on 17th November. Aaditya and Vijay produced higher grain yield on 7th December i.e. 4.93 t/ha and 4.25 t/ha, whereas Gautam yielded highest on 17th November with 4.45 t/ha. The last date of sowing produced the lowest grain yield across all the varieties. Similarly, the highest quantity of straw (6.72 t/ha) was observed in Gautam which was statistically at par with Aaditya, followed by Vijay on 7th December. Hence, 7th December for sowing Aaditya and Vijay under Tikapur condition owing to higher yields of both grain and straw whereas 17th November could be suggested for Gautam.